Identification of Physical Activity and Body Mass Index on the Incidence of Prediabetes Mellitus in High School Students - Cahyo Wibowo; Venti Agustina; Suroto Suroto (Universitas Negeri Medan, 2020)
Prediabetes mellitus is a condition of a person's blood sugar, which, if in a fasting state, ranges from 100-125 mg / dL (IFG) or 2 hours after eating, the blood sugar level is 140-199 mg / dL. Physical activity and BMI are factors that trigger prediabetes mellitus. Therefore it is necessary to hold preventive efforts to reduce the rate of development of prediabetes mellitus which is increasing and increasing public awareness regarding the importance of maintaining a healthy lifestyle. The purpose of writing this literature is to analyze physical activity and body mass index on the incidence of prediabetes mellitus in high school students. The research writing method used a literature review. Data were collected from 30 journals which were then selected into 22 journals with related variables, namely physical activity and body mass index with the incidence of prediabetes mellitus, a sample of high school students aged 15-18 years . The results of the literature review are that physical activity plays a role in controlling blood sugar and Body Mass Index (BMI) contributes to the occurrence of prediabetes if followed by an unhealthy waist circumference, less physical activity results in an increase in BMI which ultimately triggers prediabetes mellitus.